IMPLEMENTASI PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS II SD NEGERI 007 KAMPUNG BARU KECAMATAN GUNUNG TOAR - Asrawati Asrawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This study aims to improve the learning outcomes of natural science students with the application of the type of cooperative learning model of snowball throwing in class II of SD Negeri 007 Kampung Baru Kecamatan Gunung Toar. This research is a class action research that includes planning (action), action (observation), observation (observation), reflection (reflection). The subjects in this study were class II of SD Negeri 007 Kampung Baru Kecamatan Gunung Toar, amounting to 21 people consisting of 9 male students and 12 female students. The results showed, seen from the basic scores of students who completed as many as 10 people with a percentage of 47.61%. After repairs in the first cycle, student learning outcomes increased to 15 people who completed with a percentage of 71.42%. while in the second cycle again increased to 19 people who completed with a percentage of 90.47%. Based on these results it can be concluded that by applying the snowball throwing type cooperative learning model can improve the science learning outcomes of Class II of SD Negeri 007 Kampung Baru Kecamatan Gunung Toar.